Interrelationships among critical factors of work flow reliability in lean construction - Zhang, Lianying; Chen, Xi; Suo, Yongqing (Journal of Civil Engineering and Management, 2017)
Work flow in lean construction has a significant influence on project performance. Uncertain work flow will lead to waste and reduce labor productivity. Reliable work flow will contribute to improving project performance. We found twenty variables affecting work flow reliability by literature review. In order to identify critical factors of work flow reliability and explore interrelationships among them, we designed a questionnaire to collect data, applied factor analysis to identifying critical factors, and put forward hypotheses on the basis of previous research and applied structural equation model (SEM) to exploring interrelationships among the critical factors of work flow. Final model confirmed nine hypotheses and denied three hypotheses. Besides, this paper discovered other interrelationship among the critical factors except for the hypotheses. The result of this research will help project managers understand work flow easily and take effective measures to improve work flow reliability, which will contribute to implement lean construction successfully.